Challenges and opportunities for medical referrals at a mobile community health clinic serving sexual and gender minorities in rural South Carolina: a qualitative approach - Layla Joudeh; Smith F. Heavner; Ethan Johnstone; Shantara K. Propst; Orlando O. Harris (BMC, 2023)
Abstract Background Sexual and gender minorities (SGM) in the Southern United States face challenges in accessing sexual and gender affirming health care. Alternative care models, like inclusive mobile clinics, help mitigate barriers to care for SGM. There is limited data in the literature on the experience of medical referral processes for SGM individuals accessing services from mobile health clinics. Aims and objectives The purpose of this study is to describe the medical referral experiences of SGM clients and their providers at a mobile health clinic in the Southern United States. Methods We recruited English-speaking individuals who provided care or received care from the mobile health clinic in South Carolina between June 2019 and August 2020. Participants completed a brief demographic survey and a virtual in-depth, semi-structured individual interview. Data analysis was conducted using an iterative process to generate codes, categories, and themes. Data collection and analysis were terminated once thematic saturation was achieved. Results The findings from this study indicated that the mobile health clinic had an inconsistent referral process that was largely dependent on providers' knowledge. Furthermore, clients and providers expressed individual barriers to the referral process, such as financial barriers, and opportunities to improve the referral process, such as an opt-in follow-up from the mobile clinic and increased mobile clinic resources. Conclusion The findings in this study underscore the importance of having mobile clinics create a structured referral process that all medical providers are familiar with, and the value of hiring patient navigators that can support and refer clients to care that goes beyond the mobile health clinic setting.